Highly sensitive trivalent copper chelateâluminol chemiluminescence system for capillary electrophoresis chiral separation and determination of ofloxacin enantiomers in urine samples - Hao-Yue Xie; Zuo-Rong Wang; Zhi-Feng Fu (Elsevier, 2014)
A simple, fast and sensitive capillary electrophoresis (CE) strategy combined with chemiluminescence (CL) detection for analysis of ofloxacin (OF) enantiomers was established in the present work. Sulfonated Î²-cyclodextrin (Î²-CD) was used as the chiral additive being added into the running buffer of luminolâdiperiodatocuprate (III) (K5[Cu(HIO6)2], DPC) chemiluminescence system. Under the optimum conditions, the proposed method was successfully applied to separation and analysis of OF enantiomers with the detection limits (S/N=3) of 8.0Â nM and 7.0Â nM for levofloxacin and dextrofloxacin, respectively. The linear ranges were both 0.010â100Â Î¼M. The method was utilized for analyzing OF in urine; the results obtained were satisfactory and recoveries were 89.5â110.8%, which demonstrated the reliability of this method. This approach can also be further extended to analyze different commercial OF medicines. Keywords: Ofloxacin, Chiral analysis, Sulfonated-Î²-CD, Capillary electrophoresis, Chemiluminescence